Fatores de risco metabólico e obesidade em mulheres com diagnóstico de diabetes gestacional prévio e sua relação com o consumo alimentar habitual. - Coutinho, Mário de Almeida Pereira (2013)
This research aimed to examine the frequency of metabolic syndrome, obesity, glucose intolerance and type 2 diabetes mellitus and its relationship with the current food consumption in women with previous gestational diabetes. As specific objectives, identify the biochemical values associated with metabolic syndrome (MS) in the post-pregnancy, identify the presence of hypertension and evaluate the dietary composition of the food, correlating to the onset of MS. The study involved 49 women attending the outpatient clinic of Gestational Diabetes in a university hospital located in a city in northeastern Brazil, in the 2012 and 2013 years. In the postpartum period between 6 months and 4 years, participants were recruited for a consultation, where they were subjected to a questionnaire about their medical history, measurement of weight and height, eating habits, level of physical activity, as well as bioimpedance exam and laboratory tests, presented in the second consultation. This study found a high prevalence of metabolic syndrome in the order of 49%, high number compared to those found in the literature in patients with a history of gestational diabetes and in the general population. After statistical analysis, it was observed by Mann-Whitney test an relatioship between the prevalence of metabolic syndrome and a lower protein intake (p = 0.05), when the macro and micronutrients were adjusted by weight. It was also observed that the prevalence of diabetes mellitus and dysglycemias (16% and 65% respectively), numbers close to those found in studies carried out five years after pregnancy and for longer periods. No association was observed between intake of macro and micronutrients and diabetes. As for obesity, the prevalence was 28%, and only 27% were considered normal, similar to the data found in the literature. Thus, there is a high prevalence of metabolic syndrome in this population, which was associated with a reduced intake of protein.